An experimental study on the formation behavior of single and binary hydrates of TBAB, TBAF and TBPB for cold storage air conditioning applications. (1st December 2015) - Wang, Xiaolin; Dennis, Mike
Abstract: Thermal storage can be applied to air conditioning systems to shift the demand on electricity grids to decrease the peak load. It is also a feasible backup for solar cooling systems to supply on-site loads during solar outages. Although chilled water has been widely used for thermal storage, phase change materials offer greater energy storage density than chilled water. Semi-clathrate hydrates, having large heat of fusion and phase transition temperatures in the range of 5–10 °C, are proposed for thermal storage in air conditioning applications. This work presents an experimental study on the formation behavior of semi-clathrate hydrates based on tetra-n-butylammonium bromide (TBAB), tetra-n-butylammonium fluoride (TBAF) and tetra-n-butylphosphonium bromide (TBPB). The experiments vary the salt mass fraction from 10 wt% to 40 wt%. Single salt hydrates and binary salt mixtures are studied at various proportions. Furthermore, surfactant (sodium dodecyl sulfate, 0.05–0.5 wt%) and nanoparticles (TiO2, 20–80 nm) are employed to aid hydrate formation. The effect of the temperature difference driving force and memory effect on the hydrate formation are examined through consecutive formation and dissociation cycles. The formation temperature, maximum induction temperature and induction time are measured. It is observed that the supercooling and induction time differ for different salt hydrates. Both these parameters can be modified for air conditioning applications by suitable additives and proper operating conditions. Images of crystal morphology indicate that the columnar crystals of TBAB and TBAF are more compact than the hexagonal crystals of TBPB. Highlights: We determine the formation temperature of TBAB, TBAF and TBPB semi-clathrate hydrates. We examine the effect of the additives, temperature difference, and memory effect. We present sequential images of crystal morphology along the hydrate formation. The supercooling and induction time can be modified by SDS and TiO2 nanoparticles. The repeatability can be improved by proper temperature difference driving force.